Stochastic integration and one class of Gaussian random processes - Dorogovtsev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider one class of Gaussian random processes that are not semimartingales but their increments can play the role of a random measure. For an extended stochastic integral with respect to the processes considered, we obtain the Itô formula.